الجامعة الجزائرية في ظل أزمة كورونا، من ثلاثية التعليم التقليدي الى ثنائية التعليم الحداثي - بن يطو, حورية (roa, 2020)
تسعى هذه الدراسة إلى البحث في مفهوم التعليم عن بعد وضبط معاييره، ثم البحث في أهم الأسباب الرئيسية لنجاحه في الجزائر عن طريق التخطيط والتطوير، لتوضيح الاختلاف بين التعليم النظامي والتعليم الالكتروني أو التعليم عن بعد الذي يعتمد أساسا على مبدأ الاتصال المباشر عبر الأقمار الصناعية الى أجهزة الاتصال والاستقبال وشبكة الانترنيت، التي ازدهرت برامج التعليم عن بعد عبرها مؤخرا بصورة ملحوظة، من خلال استخدام المهارات والخبرات وتطبيقاتها. الكلمات المفتاحية : التعليم الالكتروني ، التعليم النظامي ، المعايير ، التواصل الرقمي ، الأزمة الصحية. Abstract This study seeks to research the concept of distance education and set its standards, then research the most important main reasons for its success in Algeria through planning and development at all levels: economic, political, social and cultural, to clarify the difference between formal education, e-learning or distance education that depends Mainly on the principle of direct satellite communication to the communication and reception devices and the Internet, which the distance education programs have flourished through recently remarkably, through the use of skills, experiences and applications.   Key words : e-learning, formal education, standards, digital communication, health crisis.